Brazing filler metal for SiC-TiB2-CrB2-ZrB2 composite ceramic, brazing part and brazing process

By using the Ti/BNi-2/Ti composite intermediate layer system in the brazing material of SiC-TiB2-CrB2-ZrB2 composite ceramic, TiC is used to react with BNi-2 and SiC to form TiC, and needle-shaped TiB whiskers are formed through the reaction between Ti and BNi-2 or TiB2, the problem of the existing Ni-based brazing material forming graphite phase and brittle silicides when brazing SiC-based composite ceramics is solved, and the high strength and high oxidation resistance of the joint are achieved.

CN119635075APending Publication Date: 2025-03-18HEFEI UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510109260.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing Ni-based soldering material generates a large amount of graphite phase and brittle silicides when brazing SiC-based composite ceramics, resulting in poor mechanical properties of the joints and the graphite phase is prone to oxidation and volatilization at high temperatures, affecting the high-temperature oxidation resistance of the joints.

Method used

The brazing material of SiC-TiB2-CrB2-ZrB2 composite ceramic is arranged in sequence from metal I (titanium foil), intermediate metal layer (BNi-2 brazing foil) and metal II (titanium foil). By adjusting the thickness of the metal layer, the atomic ratio between Ti and Ni is controlled, and TiC is used to react with Ti and BNi-2 and SiC to form TiC, eliminating the graphite phase, and forming needle-shaped TiB whiskers through the reaction between Ti and BNi-2 or TiB2, improving the joint strength and oxidation resistance.

Benefits of technology

The high strength and high oxidation resistance of the joint are achieved, the formation of brittle phase and graphite phase is avoided, and the reliability and application value of SiC-based composite ceramic brazed connectors are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119635075A_ABST
    Figure CN119635075A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite ceramic connection, and discloses a brazing filler metal for SiC-TiB2-CrB2-ZrB2 composite ceramics, a brazing part and a brazing process, the process is characterized in that the atomic ratio control of Ti and Ni is realized by adjusting the thickness of a metal layer in a brazing material, Ti can react with graphite formed by reacting BNi-2 with SiC to form TiC, so that a graphite phase in a welding seam is eliminated, and the welding quality is improved. Ti in the brazing seam and a B element in BNi-2 or a TiB2 phase in the composite ceramic can react in the connecting layer and at the interface to form needle-shaped TiB whiskers, so that the strength and the oxidation resistance of the joint are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite ceramic connection, and more specifically to a brazing connection method for SiC-TiB2-CrB2-ZrB2 composite ceramics. Background Art

[0002] In the field of high-temperature structures, the demand for material performance is growing. SiC-based composite ceramics have excellent mechanical properties, lightweight, corrosion resistance, and radiation resistance, and have great potential in the field of high-temperature structures. Therefore, they have important application value in aerospace, nuclear energy industry, and chemical industry, and will become the next generation of key materials in the field of high-temperature structures. Since large-scale and complex components are often required in actual engineering applications, the intrinsic brittleness of composite ceramic materials limits their wide application. Therefore, achieving reliable connection of SiC-based composite ceramics themselves is conducive to promoting the widespread application of such materials.

[0003] Traditional adhesives and bolt connections are not suitable for high-temperature structures. Among welding methods, arc welding, laser welding, electron beam welding and other methods are not suitable for welding high-melting-point ceramics, and diffusion welding cannot meet the needs of complex-shaped ceramic connections. Brazing, as an economical and flexible connection method, is widely used in ceramic connections and is a method suitable for complex-structure high-temperature ceramic connections.

[0004] In the brazing of ceramics, although Ag-Cu-Ti solder is widely used, the use temperature of the joint obtained by using Ag-Cu-Ti solder generally does not exceed 450°C, which limits the high-temperature performance of high-temperature ceramic materials. Ni-based, Co-based and Pd-based solders composed of transition elements as the main elements are considered to be the most suitable solders for high-temperature structures due to their excellent high-temperature performance and mechanical properties. For example, Wang (WANG Z, et al. Joining of SiC ceramics using the Ni-Mo filler alloy for heat exchanger applications [J]. Journal of the European Ceramic Society, 2021, 41 (15): 7533-7542.) et al. used Ni-Mo alloy solder to keep the temperature in the range of 1250-1400°C for 30-45 minutes to achieve the brazing connection of SiC ceramics.

[0005] At present, BNi-2 (BNi82CrSiB) is a commonly used nickel-based high-temperature brazing filler metal. However, a large amount of graphite phase and brittle silicide will be generated in the weld of SiC-based composite ceramics brazed with high-melting-point brazing fillers such as BNi-2. Through mechanical property testing, it was found that under the action of external load, the ceramic joint broke along the graphite area, and the mechanical properties of the joint were poor. In addition, due to the presence of graphite phase, the graphite in the weld is easily oxidized and volatilized in high-temperature air, and the high-temperature oxidation resistance of the joint is also poor. Therefore, the performance of brazing SiC-based ceramic connectors using existing Ni-based brazing fillers needs to be improved, and the key to improving joint performance and promoting the application of SiC-based ceramic brazed connectors is to eliminate graphite in the weld. Summary of the invention

[0006] In view of this, the present invention provides a brazing material, a brazing part and a brazing process for SiC-TiB2-CrB2-ZrB2 composite ceramics.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The first technical purpose of the present invention is to provide a brazing material for SiC-TiB2-CrB2-ZrB2 composite ceramics, wherein the brazing material is composed of metal I, an intermediate metal layer, and metal II arranged in sequence;

[0009] The metal I and the metal II are both titanium foils, and the thickness of the metal I and the metal II are both 50 to 100 μm;

[0010] The intermediate metal layer is a BNi-2 solder foil with a thickness of 30 to 50 μm;

[0011] Moreover, the thickness ratio of the titanium foil to the BNi-2 brazing filler metal foil is between 5:4 and 5:2.

[0012] The beneficial effects of the present invention are as follows: the atomic ratio of Ti to Ni is controlled by adjusting the thickness of the metal layer in the brazing material; Ti can react with graphite formed by the reaction of BNi-2 and SiC to form TiC during the welding process, thereby eliminating the graphite phase in the weld; Ti in the brazing seam can also react with the B element in BNi-2 or the TiB2 phase in the composite ceramic in situ inside the connecting layer and at the interface to form needle-shaped TiB whiskers, thereby effectively improving the joint strength and oxidation resistance.

[0013] The second technical purpose of the present invention is to provide a SiC-TiB2-CrB2-ZrB2 composite ceramic brazing part, which is obtained by brazing the brazing materials as mentioned above in a mold in the order of SiC-TiB2-CrB2-ZrB2 / Ti / BNi-2 / Ti / SiC-TiB2-CrB2-ZrB2.

[0014] The third technical purpose of the present invention is to provide a brazing process for a SiC-TiB2-CrB2-ZrB2 composite ceramic brazing part, comprising the following steps:

[0015] (1) polishing the surfaces to be welded of SiC-TiB2-CrB2-ZrB2 composite ceramic, metal I, metal II, and intermediate metal layer for standby use;

[0016] (2) ultrasonically cleaning and drying the product obtained in step (1);

[0017] (3) The SiC-TiB2-CrB2-ZrB2 composite ceramic, metal I, intermediate metal layer, metal II and SiC-TiB2-CrB2-ZrB2 composite ceramic obtained in step (2) are combined in order, and then placed in a graphite mold for brazing to obtain a SiC-TiB2-CrB2-ZrB2 composite ceramic brazed part.

[0018] It should be noted that the SiC-TiB2-CrB2-ZrB2 composite ceramics contain 15-20 vol% TiB2, 15-20 vol% ZrB2, 15-20 vol% CrB2, and the remainder is SiC. The purpose of using composite ceramics with a higher boride content is mainly to allow Ti to react with the boride to form TiB whiskers, which is beneficial to improving the joint strength.

[0019] Preferably, in step (1), the polishing requirement is that the surface roughness Ra≤15 μm.

[0020] Preferably, in step (2), the solvent used for the ultrasonic cleaning is acetone or alcohol, and the ultrasonic cleaning time is 10 to 20 minutes.

[0021] Preferably, in step (3), the thickness of the titanium foil is 50-100 μm, and the thickness of the BNi-2 foil is 30-50 μm.

[0022] Preferably, the brazing process parameters are: vacuum degree ≤ 5×10 -2 Pa, welding temperature is 1010~1120℃, holding time is 5~20min, heating rate is 5~10℃ / min, cooling rate is 5~10℃ / min, after cooling to 300℃, cool to room temperature with the furnace.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The Ti / BNi-2 / Ti composite intermediate layer system constructed by the present invention has an atomic ratio of Ti / Ni greater than 0.5, and the typical joint microstructure obtained after brazing is: composite ceramic / TiB+Ti5Si3+TiC+Ti3SiC2 / Ti2Ni+TiB / TiB+Ti5Si3+TiC+Ti3SiC2 / composite ceramic.

[0025] The properties of TiB, TiC and Ti3SiC2 formed in the connecting layer are similar to those of SiC, TiB2, CrB2 and ZrB2 in the composite ceramics. Therefore, the performance of the connecting layer is similar to that of the composite ceramics, and the residual stress of the joint will be significantly smaller than that of the joints (connecting layer) prepared by other connecting methods, which has obvious benefits in improving the reliability of the joint.

[0026] It is mainly reflected in the following aspects: 1) Compared with the traditional brazing method, this method is close to homogeneous connection and has less stress concentration; 2) Compared with the joint brazed with a single BNi-2 brazing filler metal, it avoids the formation of brittle phase Ni2Si and weakened phase graphite, which is beneficial to improve the joint strength and oxidation resistance; 3) The three-point bending strength of the obtained joint can reach more than 270MPa, and the interface bonding strength is higher than the strength of the parent material itself, such as Figure 2 As shown, the mechanical properties of the joint can be further improved by adjusting the thickness of the Ti foil, the thickness of the BNi-2 foil, and the welding process parameters.

[0027] (2) The present invention uses a composite intermediate layer to react with a composite ceramic, and then reacts with needle-shaped TiB whiskers in situ inside the connection layer and at the connection interface. The improvement effect of the needle-shaped TiB whiskers on the joint performance is reflected in the following aspects:

[0028] 1) It has a good segmentation and refinement effect on the weld structure, preventing the brittle phase from agglomerating into large pieces; 2) Whiskers grow in situ in the connection layer as a special ceramic phase, such as Figure 1 , Figure 3-5 As shown in the figure, the volume percentage of the ceramic phase in the connecting layer is increased; 3) The crack deflection, bridging, and pull-out effects caused by the interaction between the TiB whiskers and the composite ceramics at the interface can improve the mechanical properties of the joint.

[0029] (3) During the welding process, Ti reacts with SiC and TiB2 in the composite ceramic to form TiC and Ti5Si3 with fine grains and uniform distribution in the weld, which effectively inhibits grain growth, avoids the formation of graphite phase, and improves the strength and oxidation resistance of the composite ceramic brazing parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the brazed joint prepared in Example 1 of the present invention.

[0031] Figure 2 This is a diagram of the fracture position of the brazed joint prepared in Example 1 of the present invention after the bending test.

[0032] Figure 3 This is a scanning electron microscope image of the brazed joint prepared in Example 2 of the present invention.

[0033] Figure 4 This is a scanning electron microscope image of the brazed joint prepared in Example 3 of the present invention.

[0034] Figure 5 This is a scanning electron microscope image of the brazed joint prepared in Example 4 of the present invention.

[0035] Figure 6 This is a scanning electron microscope image of the brazed joint prepared in Comparative Example 1 of the present invention.

[0036] Figure 7 This is the XRD test result of the brazed joint prepared in Comparative Example 1 of the present invention.

[0037] Figure 8 This is a scanning electron microscope image of the brazed joint prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0039] Embodiment 1:

[0040] Brazing materials and processes for SiC-TiB2-CrB2-ZrB2 composite ceramics include the following steps:

[0041] (1) SiC-TiB2-CrB2-ZrB2 composite ceramics, BNi-2 brazing foil, and pure Ti foil were processed into sizes of 8 mm × 8 mm × 8 mm, 8 mm × 8 mm × 0.04 mm, and 8 mm × 8 mm × 0.05 mm, respectively;

[0042] (2) polishing the surfaces to be welded of SiC-TiB2-CrB2-ZrB2 composite ceramic, BNi-2 brazing foil, and pure Ti foil to a surface roughness Ra≤10 μm;

[0043] (3) The SiC-TiB2-CrB2-ZrB2 composite ceramic, BNi-2 solder foil, and pure Ti foil were sequentially placed in anhydrous ethanol for ultrasonic cleaning for 20 min, and then dried for later use;

[0044] (4) The materials were combined in the order of SiC-TiB2-CrB2-ZrB2 composite ceramic, pure Ti foil, BNi-2 brazing foil, pure Ti foil, and SiC-TiB2-CrB2-ZrB2 composite ceramic, and then the combination was placed in a graphite mold; the graphite mold containing the sample to be welded was placed in a vacuum furnace for brazing connection at a heating rate of 10°C / min and a vacuum degree of ≤5×10 -2 Pa, heat up to the brazing temperature of 1090℃, keep warm for 10min, then cool to 300℃ at a rate of 10℃ / min, cool to room temperature with the furnace, and obtain the brazing parts of SiC-TiB2-CrB2-ZrB2 / Ti / BNi-2 / Ti / SiC-TiB2-CrB2-ZrB2.

[0045] The brazed joint structure was examined by scanning electron microscope, and the scanning electron microscope image is shown in Figure 1 , it can be seen that the interface of the brazing joint is well connected, and the brazing material reacts with the SiC-TiB2-CrB2-ZrB2 composite ceramic to form TiB whiskers, TiC and Ti5Si3, without the generation of graphite and silicide.

[0046] The positions of the brazed joints after the three-point bending strength test were observed, and the results are shown in Figure 2 ,It can be seen that the joint breaks in the composite ceramic matrix, and the interface bonding strength is higher than the strength of the matrix itself.

[0047] Embodiment 2:

[0048] The brazing material and process for SiC-TiB2-CrB2-ZrB2 composite ceramics are different from those in Example 1 in that the thickness of the pure Ti foil is changed to 0.08 mm.

[0049] Embodiment 3:

[0050] The brazing material and process for SiC-TiB2-CrB2-ZrB2 composite ceramics are different from those in Example 1 in that the thickness of the pure Ti foil is changed to 0.1 mm.

[0051] Embodiment 4:

[0052] The brazing material and process for SiC-TiB2-CrB2-ZrB2 composite ceramics are different from those in Example 1 in that the brazing temperature is changed to 1050°C.

[0053] Embodiment 5:

[0054] The brazing materials and processes for SiC-TiB2-CrB2-ZrB2 composite ceramics are different from those in Example 1 in that the thickness of the pure Ti foil is changed to 0.1 mm and the brazing temperature is changed to 1110°C.

[0055] Embodiment 6:

[0056] The brazing materials and processes for SiC-TiB2-CrB2-ZrB2 composite ceramics are different from those in Example 1 in that the thickness of the pure Ti foil is changed to 0.1 mm and the brazing temperature is changed to 1070°C.

[0057] Embodiment 7:

[0058] The brazing material and process for SiC-TiB2-CrB2-ZrB2 composite ceramics are different from those in Example 1 in that the thickness of the pure Ti foil is changed to 0.1 mm and the holding time is changed to 5 min.

[0059] Embodiment 8:

[0060] The brazing materials and processes for SiC-TiB2-CrB2-ZrB2 composite ceramics are different from those in Example 1 in that the thickness of the pure Ti foil is changed to 0.1 mm and the holding time is changed to 15 min.

[0061] Comparative Example 1:

[0062] Brazing materials and processes for SiC-TiB2-CrB2-ZrB2 composite ceramics include the following steps:

[0063] (1) SiC-TiB2-CrB2-ZrB2 composite ceramic and BNi-2 brazing foil were processed into sizes of 8 mm × 8 mm × 8 mm and 8 mm × 8 mm × 0.04 mm, respectively;

[0064] (2) polishing the surfaces to be welded of SiC-TiB2-CrB2-ZrB2 composite ceramic and BNi-2 brazing foil to a surface roughness Ra≤10 μm;

[0065] (3) The SiC-TiB2-CrB2-ZrB2 composite ceramic and BNi-2 solder foil were sequentially placed in anhydrous ethanol for ultrasonic cleaning for 20 min, and then dried for later use;

[0066] (4) The materials are combined in the order of SiC-TiB2-CrB2-ZrB2 composite ceramic, BNi-2 brazing filler foil, and SiC-TiB2-CrB2-ZrB2 composite ceramic, and then the combination is placed in a graphite mold; the graphite mold containing the sample to be welded is placed in a vacuum furnace for brazing at a heating rate of 10°C / min and a vacuum degree of ≤5×10 -2Pa, and then heated to the brazing temperature of 1090℃, kept at this temperature for 10min, then cooled to 300℃ at a cooling rate of 10℃ / min, and cooled to room temperature with the furnace. The brazed parts of SiC-TiB2-CrB2-ZrB2 / BNi-2 / SiC-TiB2-CrB2-ZrB2 were obtained.

[0067] The brazed joint structure was tested by scanning electron microscopy and X-ray diffraction (XRD), and the results are shown in Figure 6 and Figure 7 It can be seen that the interface of the brazed joint is well connected, no TiC, TiB, Ti3SiC2 and Ti5Si3 are found, and there are residual graphite phases, microcracks and a small amount of holes in the weld.

[0068] Comparative Example 2:

[0069] The brazing material and process for SiC-TiB2-CrB2-ZrB2 composite ceramics are different from those in Comparative Example 1 in that the holding time is changed to 5 minutes.

[0070] Comparative Example 3:

[0071] The brazing material and process for SiC-TiB2-CrB2-ZrB2 composite ceramics are different from those of Comparative Example 1 in that the brazing temperature is changed to 1050°C.

[0072] Comparative Example 4:

[0073] Brazing materials and processes for SiC-TiB2-CrB2-ZrB2 composite ceramics include the following steps:

[0074] (1) SiC-TiB2-CrB2-ZrB2 composite ceramics, BNi-2 brazing foil, and pure Ti foil were processed into sizes of 8 mm × 8 mm × 8 mm, 8 mm × 8 mm × 0.04 mm, and 8 mm × 8 mm × 0.03 mm, respectively;

[0075] (2) polishing the surfaces to be welded of SiC-TiB2-CrB2-ZrB2 composite ceramic, BNi-2 brazing foil, and pure Ti foil to a surface roughness Ra≤10 μm;

[0076] (3) The SiC-TiB2-CrB2-ZrB2 composite ceramic, BNi-2 solder foil, and pure Ti foil were sequentially placed in anhydrous ethanol for ultrasonic cleaning for 20 min, and then dried for later use;

[0077] (4) The materials were combined in the order of SiC-TiB2-CrB2-ZrB2 composite ceramic, pure Ti foil, BNi-2 brazing foil, pure Ti foil, and SiC-TiB2-CrB2-ZrB2 composite ceramic, and then the combination was placed in a graphite mold; the graphite mold containing the sample to be welded was placed in a vacuum furnace for brazing connection at a heating rate of 10°C / min and a vacuum degree of ≤5×10 -2 Pa, heat up to the brazing temperature of 1090℃, keep warm for 10min, then cool to 300℃ at a rate of 10℃ / min, cool to room temperature with the furnace, and obtain the brazing parts of SiC-TiB2-CrB2-ZrB2 / Ti / BNi-2 / Ti / SiC-TiB2-CrB2-ZrB2.

[0078] The brazed joint structure was examined by scanning electron microscope, and the scanning electron microscope image is shown in Figure 8 It can be seen that the interface of the brazed joint is well connected. Although no graphite phase is found, the brazing seam is composed of only two phases, TiB and Ti2Ni, and there is no strengthening phase such as TiC and Ti5Si3.

[0079] Performance Testing

[0080] In order to compare and analyze the strength of SiC-TiB2-CrB2-ZrB2 composite ceramic joints under different processes, a three-point bending test was carried out on the SiC-TiB2-CrB2-ZrB2 composite ceramic brazed joints using a mechanical testing machine to test the room temperature bending strength of the samples. Three samples were selected from each group for the three-point bending test, and the bending strength was the average value of the bending strength of the three samples.

[0081] The bending strength data of the welded joints obtained in Examples 1-4 and Comparative Example 1 are shown in Table 1 below:

[0082] Table 1 Bending strength test results of SiC-TiB2-CrB2-ZrB2 composite ceramic brazing joints

[0083]

[0084] It can be seen from the data in the above table that the bending strength of the brazed connectors obtained by adopting the solution of the present invention is significantly higher than that of the brazed connectors obtained by adopting the solution of the comparative example.

[0085] Based on the above analysis, it can be seen that the Ti in the liquid phase of the Ti / BNi-2 / Ti composite solder layer of the present invention reacts with the composite ceramic to form TiC, TiB and Ti5Si3 during the welding process. The whisker-like TiB perpendicular to the interface enhances the joint strength, and the structure similar to the parent material reduces the thermal expansion coefficient of the brazing seam, further improving the joint strength. Compared with the single BNi-2 intermediate layer, the brazing material of the present invention avoids the formation of brittle silicide and graphite phases between Ni and the composite ceramic, thereby improving the joint strength and oxidation resistance.

[0086] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A brazing material for brazing SiC-TiB2-CrB2-ZrB2 composite ceramics, characterized in that: The brazing material is composed of titanium foil and BNi-2 brazing material foil, and the stacking method is Ti / BNi-2 / Ti; wherein, The thickness of the titanium foil is 50-100 μm, the thickness of the BNi-2 solder foil is 30-50 μm, and the thickness ratio of the titanium foil to the BNi-2 solder foil is between 5:4 and 5:

2.

2. A SiC-TiB2-CrB2-ZrB2 composite ceramic brazing part, characterized in that: The brazed part is obtained by combining the brazing materials as described in claim 1 in the order of SiC-TiB2-CrB2-ZrB2 / Ti / BNi-2 / Ti / SiC-TiB2-CrB2-ZrB2 and brazing them in a mold.

3. The SiC-TiB2-CrB2-ZrB2 composite ceramic brazing piece according to claim 2, characterized in that: In SiC-TiB2-CrB2-ZrB2 composite ceramics, the TiB2 content is 15-20 vol%, the ZrB2 content is 15-20 vol%, the CrB2 content is 15-20 vol%, and the balance is SiC.

4. A brazing process for a SiC-TiB2-CrB2-ZrB2 composite ceramic brazing piece as claimed in claim 3, characterized in that: The steps include: (1) polishing the surfaces to be welded of SiC-TiB2-CrB2-ZrB2 composite ceramic, titanium foil and BNi-2 solder foil, ultrasonically cleaning them and drying them for later use; (2) The SiC-TiB2-CrB2-ZrB2 composite ceramic, titanium foil and BNi-2 brazing foil obtained in step (1) are combined in the order of SiC-TiB2-CrB2-ZrB2 / Ti / BNi-2 / Ti / SiC-TiB2-CrB2-ZrB2, and then placed in a graphite mold for brazing to obtain a SiC-TiB2-CrB2-ZrB2 composite ceramic brazing part.

5. The brazing process of the SiC-TiB2-CrB2-ZrB2 composite ceramic brazing piece according to claim 4, characterized in that: The polishing requirement is that the surface roughness Ra≤15 μm.

6. The brazing process of the SiC-TiB2-CrB2-ZrB2 composite ceramic brazing piece according to claim 4, characterized in that: The solvent used for the ultrasonic cleaning is acetone or alcohol, and the ultrasonic cleaning time is 10 to 20 minutes.

7. The brazing process of the SiC-TiB2-CrB2-ZrB2 composite ceramic brazing piece according to claim 4, characterized in that: In step (2), the thickness of the titanium foil is 50-100 μm, and the thickness of the BNi-2 solder foil is 30-50 μm.

8. The brazing process of the SiC-TiB2-CrB2-ZrB2 composite ceramic brazing piece according to claim 4, characterized in that: The process parameters of the brazing welding are: welding vacuum degree ≤ 5×10 -2 Pa, welding temperature is 1010~1120℃, holding time is 5~20min, heating rate is 5~10℃ / min, cooling rate is 5~10℃ / min, after cooling to 300℃, cool to room temperature with the furnace.

Citation Information

Patent Citations

  • Ceramic / metal connecting method based on Ni-B / Ti instant liquid phase in-situ reaction

    CN105254321A

  • Brazing filler metal for brazing ZrB2-SiC ultrahigh-temperature ceramic and process for brazing by using brazing filler metal

    CN106112310A

  • Method for connecting graphite and stainless steel through high-temperature brazing of composite gradient intermediate layer

    CN112620851A

  • Composite interlayer for SiC ceramic connection and brazing connection method

    CN117102728A

  • Formation of tic-dispersed titanium alloy composite material and formation of tic-dispersed titanium alloy composite layer

    JP2000219924A